Malignant extra-adrenal pelvic paraganglioma in a paediatric patient - Cao, Gabriel (Ecancermedicalscience, 2017)
The extra-adrenal paraganglioma is a neoplasm originating in regional structures, uncommon in paediatrics. We report on a case of a 13-year-old patient who began with severe arterial hypertension, tachycardia, dilated cardiomyopathy and elevated levels of catecholamines in the blood and urine. The presence of a retrovesical pelvic mass in contact with the right vaginal dome was determined by imaging studies. A diagnosis of malignant extra-adrenal pelvic paraganglioma with lymph node metastases was reached through biopsy and the surgical resection of subsequent local recurrences. Paragangliomas are usually located in the paravertebral zones from the base of the skull to the retroperitoneum and are benign in 90% of cases. This kind of neoplasia is uncommon in paediatrics, especially those located in the pelvis. In cases of masses of a gynaecological origin, a differential diagnosis should be considered, and a histological and immunohistochemical study is essential in certifying the diagnosis.